Instructional Role-Playing Video Game: Its Application to Physics’ Equations of State Learning - Dolipas, Bretel; Dolipas, Thrysha; Fabrigas, Christian; Garcia, Marius; Romero, Sebastien Duke; Mactal, Aeron; Silvio, Junel (Journal of Interdisciplinary Perspectives, 2024)
The potential of video games for learning is now widely accepted among the community of Educational Technology. Multiple types of research have been conducted to see the proficiency of video games as an educational tool, and the effect on students' learning and performance of instructional video game approaches, which have elevated considerable interest in the thematic field of education research. The study assessed the effectiveness of instructional role-playing video games in learning physics equations of state concepts and problem-solving for junior high school students. Specifically, the study determined the performance level in Equations of State Problem Solving of junior high school students when concepts were taught through the conventional approach and through the Role Playing Video Game approach. The result indicated that the performance level in Equations of State problem solving of students taught using the role- playing video game approach was significantly higher than those taught using the conventional approach. Also, the Equations of State problem-solving performance level of students taught using the role-playing video game were satisfactory or better regardless of sex. Problem-solving through role-playing video games is an effective learning approach to learning the Equation of State concept. It is recommended that further research on the application of instructional Role-playing video games be considered in the teaching and learning of Physics concepts.